4D Printing Pre-Strained Structures for Fast Thermal Actuation - Zou, Yu; Huang, Zhongyi; Li, Xiying; Lv, Pengyu (Frontiers in Materials, 2021)
Four-dimensional (4D) printing is an emerging technology by adding the dimension of time-dependent reconfiguration into 3D printing. It enables the 3D printed structure to change the shape, property, or functionality under external stimuli such as temperature, magnetic field, light, etc. Among the existing 4D printed structures, thermal responsive structures are widely used for their easy operation. However, the slow actuation of the thermal responsive structures impedes the applications like soft robotics. In the current work, a pre-strained strategy is proposed to accelerate the actuation of thermal responsive structures. A 4D printing platform that can apply strain during the printing process is constructed to fabricate the pre-strained structures under the aid of in-situ tensile of the printing base. A bilayer structure with one pre-strained layer and the other non-pre-strained layer is integrally printed. Through experiments and the finite element analysis, it is demonstrated that the aspect ratio has little effect on the deformation of the bilayer structure, whereas the pre-strain plays a key role in the deformation and also greatly accelerates the actuation of the bilayer structure. Based on the 4D printed pre-strained bilayer structure, an energy-free gripper is fabricated and a fully soft crawler is printed to achieve a high running speed.